Efficiency Role of Spectrophotometer Usage for Detection of Oil Adulteration - Sakha, Mohammad Zaher (Journal of Natural Sciences – Kabul University, 2024)
Spectrophotometer is the method used for detection and measurement of light which is absorbed by molecules of a solution or passes it. Usually absorbance applied between 400-700nm. Spectrophotometer is applicable in many areas. Adulteration level in edible oils was reported 24% worldwide namely adding of cheap oils into expensive one or adding of lard in vegetable oils and dairy products. For detection of food fraud for example oils, the spectrophotometer is a precise and sensitive method and could determine less added adulterants in a sample.